Irisin is Associated with Urotensin II and Protein Energy Wasting in Hemodialysis Patients - Wan-Yu He; Fei Wu; Xin-Xin Pang; Guan-Jong Chen; La-Ta A; Lian He; Song Wang; Chao-Shu Tang; Ai-Hua Zhang (Kidney & Blood Pressure Research, 2016)
Aims/Introduction: Irisin is a newly identified myokine which can promote energy expenditure. Urotensin II (UII) is identified as the most potent mammalian vasoconstrictor to date. Previous studies showed that UII can aggravate insulin resistance while irisin alleviate insulin resistance. Through this study, it is our aim to elucidate if UII can induce insulin resistance and also have an association with the irisin level in hemodialysis (HD) patients. Materials and Methods: One hundred and twenty-eight patients on maintenance hemodialysis treatment and forty healthy subjects were enrolled in this study. Blood irisin concentrations and UII concentrations were measured by ELISA and RIA respectively. The body composition was analyzed by bioelectrical impedance. Results: The serum irisin levels and UII levels were both significantly lower in HD patients in comparison to that of the healthy subjects. The serum irisin levels were lower in HD patients with protein energy wasting than those of the patients without protein energy wasting. The independent determinants of circulating Ln (irisin) (the natural logarithm of irisin) were UII lean body mass and patients with protein energy wasting. Conclusions: Our results are the first to provide the clinical evidence of the association among irisin, UII, and protein energy wasting. Our results hint that UII and protein energy wasting might inhibit the release or synthesis of irisin from skeletal muscles in HD patients.